The effect of pre-pregnancy body mass index and gestational weight gain on pregnancy outcomes in urban care settings in Urmia-Iran - Porali Reza; Ayatollahi Haleh; Yekta Zahra; Farzin Azadeh (BMC, 2006)
Abstract Background Nutritional status of women has been considered an important prognostic indicator of pregnancy outcomes. Few studies have evaluated patterns of weight gain and pre-pregnancy body mass index in developing regions where malnutrition and poor weight gain as well as maternal obesity have significant influences on the pregnancy outcome. This study aims to show effect of pregnancy body mass index and the corresponding gestational weight gain on the outcome of pregnancy. Methods On a prospective cross sectional study, two hundred and seventy women from urban areas of Northwest Iran were recruited for participation during their first eight weeks of pregnancy. Body mass index (BMI) was categorized and gestational weight gain was divided into two groups of normal and abnormal based on recommendations of Institute of Medicine (IOM) published in 1990. Chi square and one way ANOVA were used in the univariate analysis of the association between weight gain and corresponding adverse outcomes including cesarean, preterm labor and low neonatal birth weight. Adjusted odds ratios for adverse outcomes were determined by multiple logistic regression models, while controlling for the following factors: maternal age, parity, and education. Results Both pre-pregnancy BMI < 19 and abnormal weight gain during pregnancy were found to be associated with low neonatal birth weight defined as < 2500 g. Abnormal weight gain, during pregnancy was not related to an increased risk of preterm labor or cesarean delivery but it was highly associated with low birth weight (LBW)(P < 0.05). Conclusion Low pre-pregnancy BMI is an established risk factor for LBW. Abnormal gestational weight gain may further complicate the pregnancy as an additional risk factor for neonatal LBW. All women, regardless of their pre-pregnancy BMI may be at risk for abnormal weight gain and hence low birth weight. Pre-pregnancy and gestation nutritional assessments remain significant part of all prenatal visits.